Perfil antropométrico e desempenho motor de atletas de basquetebol universitário - Silva, Elvyn Pedro Serrão da (2024)
The study aimed to characterize the anthropometric profile and physical fitness of basketball athletes who participated in university games held at the Federal University of Amazonas. This research is characterized as descriptive and exploratory, involving a sample of 15 athletes, 9 male and 6 female. Anthropometric measurements of height, wingspan, and body weight (body composition) were performed using a bioimpedance scale (% fat; % muscle mass; visceral fat). The motor performance tests performed were: sit-and-reach test (flexibility), 1-minute modified sit-up (muscular strength endurance), 30-meter linear sprint (speed), 12-minute running test (aerobic endurance), horizontal jump test (horizontal jump strength), vertical strength test (vertical jump strength), and handgrip test (upper limb strength). The results showed that the players' body fat percentage was high, compromising the quality of the results of the 12-minute running, horizontal jump strength, vertical jump strength and sprint tests. It is necessary to increase the training of motor skills, flexibility, muscular strength endurance, horizontal jump strength, vertical jump strength and displacement speed. The male athletes presented differences in strength between the left and right hands, evidencing possible cases of muscular imbalance, which may compromise the accuracy of the throws. In conclusion, the research fulfilled its objective by characterizing the anthropometric profile and determining the level of physical fitness of athletes who participated in the UFAM university games. The need for greater focus on training related to physical fitness attributes was confirmed.